MUCOVISCIDOSIS A GENETIC DISEASE OF THE EXOCRINE GLANDS AND MANIFESTED AS A PATHOLOGY OF THE RESPIRATORY ORGANS - Boynazarov Abbosjon Anvarovich; Khabibova Nazira Nasullaevna (Web of Journals Publishing, 2025)
Cystic fibrosis (CF), also called mucoviscidosis, is an autosomal recessive genetic disease that affects the exocrine function of the lungs, liver, pancreas, small bowel, sweat glands, and urogenital system. The condition causes thick mucus and other fluids to build up and clog different parts of the body, including the lungs and digestive tract. When mucus accumulates in the lungs of people with mucoviscidosis, it can cause frequent lung infections, which over time can cause severe damage to the lungs and inhibit breathing.
Keywords: Mucoviscidosis, viscous mucus, dry cough, pneumonia, chromosome 7, cystic fibrosis transmembrane regulator (CFTR) gene.